Isolamento de bactérias ácido lácticas com atividades antimicrobiana, proteolítica e lipolítica de leite de ovelha e derivados - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This work aimed to isolate lactic acid bacteria from raw sheep milk and sheep milk products and to characterize this microbiota with a focus on antimicrobial, proteolytic and lipolytic activities. The samples were obtained from Serra Gaúcha, in a dairy that processes sheep milk and four dairy farms, and collected raw milk, pasteurized milk, pasteurized cream and butter, totaling 14 samples. Isolation was done on Man Rogosa and Sharpe Agar, followed by Gram stain and catalase test. Gram positive and catalase negative isolates were characterized as lactic acid bacteria, and evaluated the fermentative profile, proteolytic, lipolytic and antimicrobial activities against Listeria monocytogenes, Escherichia coli O157: H7 and Staphylococcus aureus. Lactic acid bacteria counts were higher in raw milk in the dairy tank, with 7.35 ± 0.11 logUFC/mL, and milk collected at property 4 8.91 ± 0.05 logUFC/mL, In which adequate practices were observed in the pre- and post-milking procedures. 253 isolates were obtained in Man Rogosa and Sharpe Agar, and among the 37 lactic acid bacteria, 19 presented some type of proteolytic, lipolytic or antimicrobial activity against Listeria monocytogenes ATCC 7644, most of which originated from raw milk. Among the isolates of lactic acid bacteria (n = 37), 48.65% (n = 18) presented proteolytic activity, 13.51% (n = 5) lipolytic activity, 10.81% (n = 4) Proteolytic activity, and only 2.70% (n = 1) presented antimicrobial activity. The results demonstrated the isolation of lactic acid bacteria from sheep milk products and derivatives with technological potential for the development of cultures for application in the processing of fermented sheep dairy products.
Keywords: BAL; Leite ovino; Ação antimicrobiana; Bactérias proteolíticas e lipolíticas; LAB; Ovine milk; Antimicrobial action; Proteolytic and lipolytic bacterias; CNPQ::CIENCIAS AGRARIAS